The Study of Japanese Women in the Facial Treatment Advertisement: A Semiotics Perspective of Pierce’s Theory - Citra Andini; Somadi Sosrohadi; Fairuz Fairuz; M. Dalyan; Fakhriawan Fathu Rahman; Hasnia Hasnia (Hasanuddin University, 2022)
This study aims to reveal the beauty standards of Japanese women in the Facial Treatment Essence SK II advertisement and to describe the slogan “Rasakan kekuatan PITERA untuk kulit tampak sebening kristal” in the Facial Treatment Essence SK II advertisement so that it can influence consumers. Meanwhile, the beauty of cosmetic users is always physically visible, even the model to introduce this product is Imma, a virtual model girl created by CGI (Computer-generated Imagery). Some of the advantages in this product are visualized by Imma, namely bright and glowing white skin. Imma has become an icon for this product because the advantages that it offers are all seen in Imma, and the standard of beauty described by Japan and the way to be beautiful like this virtual model girl is to apply the Facial Treatment Essence SK II product. This research uses a qualitative descriptive method to analyze data which maps which include icons, indexes and symbols. The result of this research indicates that the Japanese beauty standards shown by this ad are like Imma and to have skin like her, the right skincare is Facial Treatment Essence SK II and according to its slogan,